How to Make Rural Education Research Rural: An Essay at Practical Advice - Craig B. Howley (Journal of Research in Rural Education, 1997)
The sovereignty ofthe nation state, even in the developed world, is more problematic than at any time since 1945. In that light, this essay maintains that nation-building, partly through systems of schooling, has served rather more to debase than improve the rural circumstance. It suggests that a different logic of improvement is needed in rural education, but refrains from prescriptions. Instead, discussion focuses attention on the sort ofquestions that researchers (and school improvers) might ask either to discover or to invent varieties ofthat different logic. The essay distinguishes local from cosmopolitan interests and provides examples ofissues that exhibit the distinction. I remind readers that the word "essay" indicates tentativeness.